Pelecehan Anak, Kepuasan Pernikahan, dan Konseling Pranikah: Bagaimana Hubungannya Satu Sama Lain? - Hadiarni; Mariah, Kiki; Wenda Asmita (Universitas Islam Negeri Madura, 2024)
One of the reasons for the increase in child abuse in recent years is the actions of those closest to the child, including one or both of their parents. Parents who commit such violence are triggered by several factors, including lack of insight into married life and not getting satisfaction in their marriage. This study aims to describe how premarital counseling can promote marriage satisfaction and anticipating potential child abuse. This study uses literature research with a descriptive approach. This research concerns with systematic and scientific collection of library sources which include books, scientific journals, and related research findings, then analyzed descriptively so as to achieve the research objectives. The results of the discussion show that in premarital counseling, the materials are provided comprehensively which includes the Law on Domestic Violence. Child Protection Law, Munakahat Law, Implementation of Family Functions in Child Protection, Caring for Love in the Family and Conflict Management in the Family as recommended by the Director General of Islamic Community Guidance Regulation Number 542 of 2013. By understanding comprehensively and applying such recommended points, prospective partner can achieve their marriage satisfaction and minimize potential child abuse.